'A glimmer of hope': perceptions, barriers, and drivers for medicinal cannabis use amongst Australian and New Zealand people with endometriosis - a qualitative study - Justin Sinclair; Jason Abbott; Antonina Mikocka-Walus; Cecilia Ng; Jerome Sarris; Subhadra Evans; Mike Armour (Bioscientifica, 2023)
Previous quantitative research has shown that cannabis use, mostly illicit, is used for symptom management amongst those with endometriosis living in Australia or New Zealand, but the drivers and barriers for use of legal, medicinal cannabis in this population are currently unclear. This study sought to investigate, via online focus groups, the perceptions, barriers, drivers, and experiences associated with cannabis use, whether legal or illicit, amongst 37 Australians and New Zealanders, aged 18-55, with a medical diagnosis of endometriosis. Previous cannabis usage was not required to participate. Discussion topics included strategies employed to manage symptoms, exploration of current medications, previous use of cannabis for pain management, and interest in using medicinal cannabis as a management strategy. Participants with moderate-to-severe symptoms of medically diagnosed endometriosis reported inadequacies with their current medical and self-management strategies and were inclined to try medicinal cannabis, both as part of their medical management and as part of a clinical trial. Barriers to medicinal cannabis adoption identified in this cohort included high costs of legal cannabis products, lack of clarity and fairness in current roadside drug testing laws and workplace drug testing policies, concern over the impact of stigma affecting familial, social and workplace life domains, and subsequent judgement and the lack of education/engagement from their medical providers regarding cannabis use. Given the interest in medicinal cannabis and the reported lack of effective symptom management, clinical trials are urgently required to determine the potential role that medicinal cannabis may play in reducing the symptoms of endometriosis.